Refractory Celiac Disease - Malamut, Georgia; Cerf-Bensussan, Nadine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is about recurring celiac disease its diagnosis and management. It starts by discussing the pathogenesis of refractory celiac disease and the role of viruses, microbiota and genetics in this disease. It also covers the epidemiological aspects. Refractory Celiac Disease is a unique resource on the topic written by a team of international experts in the topic and will be of great use to gastroenterologists and researchers in the field.
1. Introduction -- 2. Pathogenesis of refractory celiac disease (I): role of virus and microbiota -- 3.Pathogenesis of refractory celiac disease (II): from refractory celiac disease to overt lymphoma -- 4. Pathogenesis of refractory celiac disease (III): genetic basis.-5. From unresponsive celiac disease to refractory celiac disease -- 6. Epidemiology of refractory celiac disease -- 7. Diagnosis of refractory celiac disease: Isolation-flow phenotyping and clonality -- 8.Diagnosis of refractory celiac disease: pathology -- 9. The other causes of severe enteropathy with villous atrophy non responsive to a gluten free diet -- 10.Treatment of Refractory Celiac disease.
Keywords: Internal medicine; Immunology; Internal Medicine; Internal Medicine; Immunology; Celiac Disease -- physiopathology; Celiac Disease -- therapy; Enteropathy-Associated T-Cell Lymphoma